TYPES OF FLAGELLATES WITH A PLANT TYPE OF EXCHANGE AND TYPES OF FLAGELLATES WITH AN ANIMAL TYPE OF EXCHANGE - JYOTI RASHMI (International Journal of Multidisciplinary Research and Studies, 2020)
Flagellates are a diverse group of single-celled organisms that have one or more whip-like structures called flagella, which they use for movement. Some flagellates have a plant-like mode of exchange, while others have an animal-like mode of exchange. Flagellates with a plant-type exchange are photosynthetic, meaning they can produce their own food through photosynthesis. This process involves using sunlight to convert carbon dioxide and water into glucose and oxygen. Examples of flagellates with a plant-type exchange include Euglena and Chlamydomonas. Euglena is a freshwater flagellate that has both plant-like and animal-like characteristics. It has chloroplasts, which allow it to carry out photosynthesis and produce its own food, but it also has a primitive mouth that it uses to ingest other organisms when light is scarce. Euglena can switch between these two modes of exchange depending on the availability of light and nutrients. Chlamydomonas is another freshwater flagellate that is primarily photosynthetic. It is a unicellular green algae that has a single chloroplast and a single flagellum. Chlamydomonas is an important model organism for studying photosynthesis and cell biology.